A LASER SYSTEM FOR THE CONTROL OF THE COMPLEX FOR THE CONSTRUCTION OF MINI - Bulgakov, Alexey Grigoryevich; Vakolyuk, Alexander; Glebov, Nikolay; Bienkowski, Natalia (Journal of Applied Engineering Science, 2017)
This article describes a laser system for the control and controlling of mini shields in a tight urban development. The direction of movement of the mini shield at the start point is set with the aid of a beam generated by the source of laser radiation. Using the same source is transferred to the service information from the operator's console for the equipment mini shield. On mini shield installed equipment defining two points mini shield relative to the laser beam, as well as take on the connection information. Information on the operator panel are transmitted using a second laser emitter mounted on a mini shield.